2019
DOI: 10.1155/2019/1910624
|View full text |Cite
|
Sign up to set email alerts
|

BeautyNet: Joint Multiscale CNN and Transfer Learning Method for Unconstrained Facial Beauty Prediction

Abstract: Because of the lack of discriminative face representations and scarcity of labeled training data, facial beauty prediction (FBP), which aims at assessing facial attractiveness automatically, has become a challenging pattern recognition problem. Inspired by recent promising work on fine-grained image classification using the multiscale architecture to extend the diversity of deep features, BeautyNet for unconstrained facial beauty prediction is proposed in this paper. Firstly, a multiscale network is adopted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 31 publications
(36 reference statements)
0
23
0
Order By: Relevance
“…7 illustrates key differences between conventional machine learning and transfer learning. Transfer learning can address small datasets, leading to augmenting model learning performance [61,62]. Fine-tuning of trained models allows adaptation to problems to be achieved [63].…”
Section: Deep Learning With Transfer Learning and Image Augmentationmentioning
confidence: 99%
“…7 illustrates key differences between conventional machine learning and transfer learning. Transfer learning can address small datasets, leading to augmenting model learning performance [61,62]. Fine-tuning of trained models allows adaptation to problems to be achieved [63].…”
Section: Deep Learning With Transfer Learning and Image Augmentationmentioning
confidence: 99%
“…It achieves an effective and simple feature fusion technique through ECCV HotOrNot and SCUT-FBP datasets. Zhai et al [46] showed promising results on fine-grained image classification using a multi-scale architecture to increase diversification among the deep features using BeautyNet to predict unconstrained facial beauty. A multi-scale network was used to enhance the discriminative features of the face.…”
Section: Bfp and Transfer Learningmentioning
confidence: 99%
“…A small portion of beautiful faces exists in databases, with most of the faces generated from confined ethnic groups. Previous findings have shown that deeper representation has higher efficient performance than inadequate ones [46,57]. The solution to this inadequacy is to employ state-of-the-art techniques such as data augmentation or transfer learning so as to improve the most and least attractive faces [21], [22], [47].…”
Section: Some Challenges In Facial Beauty Analysis and Predictionmentioning
confidence: 99%
“…Datasets There are a variety of benchmark datasets for scoring images: The AVA dataset [27], the Hot-Or-Not dataset [19], the SCUT-FBP dataset [16], the LSFCB dataset [20], the London Faces Dataset [13], and the CelebA dataset [28]. The AVA dataset [27] doesn't have attractiveness ratings for the subject, instead they have an attractiveness rating for the entire image i.e.…”
Section: Related Workmentioning
confidence: 99%